Dietary Malic Acid Supplementation Induces Skeletal Muscle Fiber-Type Transition of Weaned Piglets and Further Improves Meat Quality of Finishing Pigs - Zhang, Xin; Chen, Meixia; Yan, Enfa; Wang, Yubo; Ma, Chenghong; Zhang, Pengguang; Yin, Jingdong (Frontiers in Nutrition, 2022)
The aim of this study was to investigate effects of dietary malic acid supplementation on skeletal muscle fiber-type transition during nursery period and the subsequent meat quality of finishing pigs. Results showed that malic acid supplementation for 28 d increased oxidative fibers percentage of weaned piglets, accompanied by the increased aerobic oxidation in serum and longissimus thoracis (LT) muscle. Additionally, activities of total antioxidant capacity and glutathione peroxidase in serum were increased. Moreover, dietary malic acid supplementation during nursery period tended to increase pH24h and significantly decreased drip loss in LT muscle of finishing pigs. The content of total saturated fatty acid (SFA) and total monounsaturated fatty acid in LT muscle was significantly decreased, while the ratio of polyunsaturated fatty acid to SFA tended to increase. Together, dietary malic acid supplementation during nursery period can effectively increase antioxidant capacity and oxidative fibers percentage of weaned piglets, and further improve water holding capacity and nutritional values of pork in finishing pigs.